Damphu: The Symbol of Tamang Cultural Identity - Lama, Kumari (Mindscape: A Journal of English & Cultural Studies, 2023)
Damphu, a musical instrument, embodies specific meaning in Tamang community. Since damphu is compulsorily played on the auspicious occasions, marriage, cultural ceremony and festivals, it always remains at the center of Tamang cultural values. There is an interesting story of the creation of Damphu. Tamba (Spokesperson of Tamang community) narrates the story of Pengdorje (Tamang ancestor), who created the musical instrument collecting different materials from the forests of high hill, mountain and madesh, through his song. Damphu is an important symbol of Tamang cultural identity, which is also taken as the source of Tamang knowledge and aesthetics. Against the backdrop, the paper sheds light on the creation of damphu and analyzes its cultural significance on the basis of Shantabir Lama’s (Pakhrin) book Tamba, Kaiten, Wai, Rimthim: The Tamang Ancestor’s Culture and Song (2014). I have employed Clifford Geertz’s cultural interpretation that emphasizes culture as a set of ‘control mechanism’ for the theoretical backing. On top of that, I have also consulted Amrit Yonjan- Tamang’s idea of Tamba philosophy to deal with Tamang cultural aesthetics.